TI_GERICHTE 52.2022.318 vom 31. August 2022 , Licenza edilizia per la formazione di un muro di sostegno con opere di cinta - TI Tribunale d'appello (2022)
Licenza edilizia per la formazione di un muro di sostegno con opere di cinta